1996
DOI: 10.1128/jb.178.4.1012-1017.1996
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate genetic regulation of glycogen catabolism and biosynthesis in Escherichia coli via the CsrA gene product

Abstract: The carbon storage regulator gene, csrA, encodes a factor which negatively modulates the expression of the glycogen biosynthetic gene glgC by enhancing the decay of its mRNA (M. Y. Liu, H. Yang, and T. Romeo, J. Bacteriol. 177:2663-2672, 1995). When endogenous glycogen levels in isogenic csrA ؉ and csrA::kanR strains were quantified during the growth curve, both the rate of glycogen accumulation during late exponential or early stationary phase and its subsequent rate of degradation were found to be greatly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
145
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(152 citation statements)
references
References 29 publications
7
145
0
Order By: Relevance
“…By inference, products of carbon metabolism downregulate CsrA activity and glycolytic flux through the Embeden-Meyerhof-Parnas pathway, while they activate gluconeogenesis, glycogen synthesis, synthesis of the biofilm exopolysaccharide dPNAG, and pathways and processes favoring stress resistance and survival, which are repressed by CsrA (Fig. 10) (7,17,18,22,24,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By inference, products of carbon metabolism downregulate CsrA activity and glycolytic flux through the Embeden-Meyerhof-Parnas pathway, while they activate gluconeogenesis, glycogen synthesis, synthesis of the biofilm exopolysaccharide dPNAG, and pathways and processes favoring stress resistance and survival, which are repressed by CsrA (Fig. 10) (7,17,18,22,24,33).…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, CsrA activates glycolysis and central carbon pathways (7)(8)(9)(10)(11)(12)(13) and motility (14,15). Conversely, it represses gluconeogenesis (7), glycogen biosynthesis (16)(17)(18)(19)(20), biofilm formation (21)(22)(23)(24), the stringent response (25), and expression of genes involved in other stress resistance and stationary-phase processes, e.g., cstA, hfq, cel, sdiA, and nhaR (24,(26)(27)(28)(29)(30). Its effects on pathogenesis are complex.…”
mentioning
confidence: 99%
“…The role of CsrA in procaryotic metabolism and physiology is just beginning to be understood. It is a negative regulator of certain processes associated with the early stationary phase of growth, including glycogen synthesis and catabolism (1,5), and gluconeogenesis (1,4) in E. coli, and the expression of several extracellular virulence factors in E. carotovora (6,7). CsrA also modulates the glycolytic pathway in E. coli (4), affects cell surface properties (1), and has been proposed to directly or indirectly affect DNA gyrase activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in vivo have indicated that the CsrA gene product facilitates the decay of glgCAP mRNA, which encodes two enzymes required for glycogen biosynthesis and the enzyme glycogen phosphorylase (3,5). The CsrA gene product is a 61-amino acid protein whose deduced amino acid sequence contains a conserved RNA-binding motif, KH (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation